Pembinaan kelompok petani budidaya melalui kegiatan aplikasi teknik probiotik dan pembuatan pakan berbasis bahan lokal pada Budidaya Ikan Lele di Kelurahan Tangkerang Utara Kecamatan Bukit Raya Kota Pekanbaru - Usman M Tang; Niken Ayu Pamukas; Adelina Adelina; Iesje Lukistyowati; Mulyadi Mulyadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
The livelihoods of the people of Tangkerang Utara Village are; in agriculture, plantation, animal husbandry, self-employment and fisheries. In the fisheries sector, there are two groups of fish cultivators (POKDAKAN) in this kelurahan, namely; POKDAKAN Cahaya Utara Mandiri and Dolphin Farm, which conduct fish farming in soil and cement ponds and cages. The main problems faced by POKDAKAN are the limited availability of water intended for fish cultivation and the wate rquality that is not suitable for catfish growth. Throught his program of guided villages, knowledge and technology is given on the technique of applying probiotics to cultivation media to improve wate rquality and minimize water use. The method used in the community service activities of the Assisted Village is the method of lecturing, discussion and direct practice in the pools owned by POKDAKAN members. The results of the evaluation of 23 extension participants showed that 20 people (86.96%) had never known about the application of probiotics in cultivation media, while 2 people (8.70%) had known about the application of probiotics and 1 person (4.34%) had apply it to catfish farming ponds. After participating in this training activity, there was an increase in knowledge about the application of this probiotic by 69.57%. Meanwhile, 22 participants understood the dosage and frequency of feeding, and all participants had already known the criteria for healthy fish seeds. The partners' assessments of the implementation of this activity are: 52.17 strongly agree that this probiotic application can be done independently; 52.17% strongly agree that probiotic applications can improve water quality; 60.87% strongly agreed that it could be an alternative livelihood; 65.22% strongly agree to speed up the maintenance period.